2012
DOI: 10.1111/j.1469-1809.2012.00728.x
|View full text |Cite
|
Sign up to set email alerts
|

Shared Genomic Segment Analysis: The Power to Find Rare Disease Variants

Abstract: Summary Shared genomic segment (SGS) analysis is a method that uses dense SNP genotyping in high-risk pedigrees to identify regions of sharing between cases. Here, we illustrate the power of SGS to identify dominant rare risk variants. Using simulated pedigrees, we consider 12 disease models based on disease prevalence, minor allele frequency, and penetrance to represent disease loci that explain 0.2% to 99.8% of total disease risk. Pedigrees were required to contain ≥15 meioses between all cases and to be hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 28 publications
(34 reference statements)
0
33
0
Order By: Relevance
“…Of note, the 9 affected subjects shared by cluster 1 and 3 fell in a multiplex pedigree (K1584) previously identified by epidemiological studies in Palau [27]. SSA [34,35] was used to determine if 4q28.3 is the only region of the genome thus shared among these 11 and 9 affected subjects. For these affected subjects, only the same 4q28 region was identified (fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, the 9 affected subjects shared by cluster 1 and 3 fell in a multiplex pedigree (K1584) previously identified by epidemiological studies in Palau [27]. SSA [34,35] was used to determine if 4q28.3 is the only region of the genome thus shared among these 11 and 9 affected subjects. For these affected subjects, only the same 4q28 region was identified (fig.…”
Section: Resultsmentioning
confidence: 99%
“…A statistic of some utility for pedigree-based linkage analysis is the total number of meioses separating all affected subjects in the pedigree [see [34], [35]]. Counting meioses in a pedigree is straightforward.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Results indicated that if families had at least 15 meioses between cases, 3-10 families were sufficient to gain excellent power (>80%) to see at least one true positive within any given family. For all scenarios considered, genome-wide association studies would have had negligible power.…”
Section: Sample This Project Is Possible Because Of a 20-year Collabmentioning
confidence: 99%
“…Genomewide association is well-suited to high-density SNP arrays, however, the power for this approach lies with the existence of high LD between a SNP on the platform and the underlying risk variant; which is vastly reduced with rare risk variants leading to low power [4,5]. Identity-by-descent (IBD) mapping, such as shared genomic segment (SGS) analysis, in extended pedigrees have been developed precisely for use with high-density SNP platforms and have been suggested to be more powerful than association analysis and traditional linkage analysis for the identification of rare variants [3,6,7]. The probability of IBD is a challenge to calculate in large pedigrees.…”
Section: Introductionmentioning
confidence: 99%